Fecal calprotectin levels are elevated in transthyretin amyloidosis patients with gastrointestinal manifestations. Issue 11 (March 2020) - Nakov, Radislav; Sarafov, Stayko; Nakov, Ventsislav; Gospodinova, Mariana; Ianiro, Gianluca; Todorov, Tihomir; Todorova, Albena; Tournev, Ivailo
Abstract : Abstract: Transthyretin amyloid (ATTR) amyloidosis is a rare systemic disorder characterized by amyloid deposits formed by misfolded monomers of the transthyretin. Gastrointestinal (GI) manifestations are common in ATTR amyloidosis; however, their pathogenesis is not fully elucidated. In the present study, we aim to evaluate the diagnostic role of fecal calprotectin (FC) in ATTR amyloidosis patients with GI manifestations. We recruited 21 consecutive ATTR amyloidosis patients and 42 sex and age-matched healthy controls. The presentation of GI symptoms and the severity of peripheral neuropathy were evaluated. Colonoscopy and FC assessment were performed in all subjects. Mean levels of FC in ATTR amyloidosis patients (184 μg/g [30–430]) were significantly higher thаn those of controls (40 μg/g [30–70]), P  < .001. Receiver operating characteristic curve analysis indicated a FC cut-off level of 71 μg/g, which differentiates ATTR amyloidosis with GI manifestations from healthy subjects with 91% sensitivity, 100% specificity, 100% positive predictive value, 95% negative predictive value and 97% overall accuracy. FC values were significantly associated with the presence of neutrophilic granulocytic infiltration in the colonic mucosa ( P  = .002), with the presence of amyloid deposits in rectal mucosa ( P  = .007) and the presence of diarrhea ( P  = .046). FC levels are elevated in patients with ATTR amyloidosis with GI manifestations, which suggests an inflammatory component in the pathogenesis of the disease. The presence of elevated FC concentrations could help gastroenterologists to include ATTR amyloidosis in their diagnostic work-up.